2011
DOI: 10.1094/pdis-09-10-0624
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Potato yellowing virus (Genus Ilarvirus) in Solanum phureja from Ecuador

Abstract: A bacilliform virus, named Potato yellowing virus (PYV), causing chlorosis of leaves was reported in 1992 in potato (Solanum tuberosum) fields in Peru (1) and symptomless wild potatoes (S. fernandezianum) in Chile (4). PYV is reported as an alfamo-like virus (1) (family Bromoviridae) but no sequence information is available for this virus, making its taxonomic position inside the Bromoviridae uncertain (currently this family is organized into five genera: Alfamovirus, Bromovirus, Cucumovirus, Ilarvirus, and Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The virus was later renamed potato yellowing virus [29, 30, 31]. In subsequent studies, PYV was reported on potato and pepper plants from Chile and Ecuador with only partial sequence information provided [32, 33] covering less than 1 kb of the genome. Our PYV isolate (PV-0706) was obtained from a pepino fruit ( Solanum muricatum ) of unknown geographic origin purchased in a German supermarket and was propagated on D .…”
Section: Discussionmentioning
confidence: 99%
“…The virus was later renamed potato yellowing virus [29, 30, 31]. In subsequent studies, PYV was reported on potato and pepper plants from Chile and Ecuador with only partial sequence information provided [32, 33] covering less than 1 kb of the genome. Our PYV isolate (PV-0706) was obtained from a pepino fruit ( Solanum muricatum ) of unknown geographic origin purchased in a German supermarket and was propagated on D .…”
Section: Discussionmentioning
confidence: 99%
“…phureja in Ecuador (Silvestre et al 2011). The first complete PYV genome sequence was obtained in 2019 using HTS of sequences enriched by immunocapture of virions (Knierim et al 2019).…”
Section: Phureja S Tuberosum S Muricatum S Quitoense C Annuum and The...mentioning
confidence: 99%
“…The RNA dependent RNA polymerase gene (RdRp) was used for a phylogenetic analysis using BEAST under the LG+G model and a strict molecular clock. The phylogeny showed that the PYV isolate from naranjilla clustered with an isolate described in pepper from the same location in Tumbaco (KP772263) (Sivaprasad et al 2015), but was distantly related with isolates from Solanum phureja from other locations in Ecuador (Silvestre et al 2011) Moreover, the PYV RNAs have 80.1, 78.1 and 73.5 identity with Fragaria chiloensis latent virus, (NC_006566, NC_006567, NC_006568) which confirms that PYV as a distinct Ilavirus (family Bromoviridae). To our knowledge, this is the first report of PYV infecting S. quitoense as a new host.…”
mentioning
confidence: 57%